Uso de multicamadas de NbN/MoS2 para proteção contra corrosão e desgaste do aço inoxidável AISI 316L - Mattos, Christian Ferreira (2021)
The search for new technical solutions in surface coatings for tribological applications in industry, requires the development of multifunctional materials that meet the challenges. Monolithic coatings may not be enough to meet the increasingly aggressive demands of the market, so thin multilayer film to coat surfaces has been an attractive study for many researchers. Concepts for depositing such advanced coatings can be systematically developed through processes such as: PVD - Physical Vapor Deposition or CVD - Chemical Vapor Deposition. In this work, it was proposed to study the use of niobium nitride and molybdenum disulfide (NbN and MoS2, respectively) to act as a protective coating. NbN has characteristics of good thermal stability, high melting point, mechanical properties such as high hardness, high modulus of elasticity and good wear resistance. MoS2, on the other hand, was selected because it is a material known as a great solid lubricant and can have a great potential in increasing wear resistance, also acting as a bonding layer in the multilayer system. Thin multilayer films were deposited using the Magnetron Sputtering DC process for MoS2 and Magnetron Sputtering RF for NbN, varying the thickness of the layers, always initiating deposition with NbN, and alternating as layers in such a way that the surface contact is MoS2. In addition, the use of any layer of adhesion to the substrates was not carried out, namely: glass, silicon (100) and AISI 316L stainless steel. The analysis of SEM and EDS, combined with XRD, allows the determination of the periodicity of the layers, thickness of the individual layers, crystallinity and chemical composition. The fretting wear test calculates the wear coefficient and the wear rate. The IHT hardness test enabled the determination of mechanical properties, such as elasticity and hardness modulus and with a corrosion analysis it was possible to calculate the loss of mass.